Development of Simulated Wound Fluids. Investigating mass transport and aggregation of proteins in a wound exudate model - Nilsson, Ida (My University, 2025)
This Master’s thesis, carried out in collaboration with Mölnlycke Health Care, investigated the aspect of protein aggregation in simulated wound fluids (SWFs) in comparison to a serum-containing solution (SCS). The primary focus was on a fluid called SWF A, developed by Mölnlycke Health Care as a potential standard test fluid for evaluating wound care products. SWF A is intended to mimic biological wound exudate in terms of wetting, spreading, and drying behavior within a wound dressing, which involves a wide range of physico-chemical properties. SWF A has demonstrated strong similarities to SCS 1, a fluid known to closely mimic biological exudate, in various tests, especially those where a product is exposed to excessive amounts of fluid. However, in the more complex and clinically relevant method FLUHTE, where the spreading of a fluid within a wound dressing is assessed, SWF A has been observed to differ from SCS 1 under certain conditions, especially in more advanced multilayer foam dressings. To better understand these differences, the aggregation of BSA (Bovine Serum Albumin) in SWF and the diverse mixture of serum proteins in SCS was assessed, primarily using DLS (Dynamic Light Scattering). The results demonstrated that wound fluids represent a complex system for protein aggregation, where proteins should be regarded as active particles interacting in various ways with their environment. Three main conclusions could be drawn: (i) Protein aggregation was found to significantly influence the spreading patterns of fluids within a wound dressing. A high aggregation propensity correlated with increased clogging of the dressing and fluid being forced upward within the product, whereas low aggregation propensity resulted in fluid spreading in the direction of gravitational force. (ii) The ionic composition of a fluid had a major impact on protein aggregation, with the formation of insoluble salts likely serving as nucleation points. (iii) Electrolyte composition is not the only factor in serum that affects protein aggregation, as the protein aggregation in SCS 1, despite having the same ionic environment as SWF, still occurred differently. Although no conclusive solution for regulating protein aggregation within SWF was reached, the combined results from this study will hopefully provide a solid foundation for further research within the area of protein aggregation in simulated wound fluids.
Keywords: wound fluid; protein aggregation; bovine serum albumin; BSA; serum proteins; wound care products; peptone water; aggregates; mass transport; wound dressings; spreading pattern; serum-containing solution; SCS; DLS; precipitation